Users' continuance intention to use a mobile application: Adapting store personality as application personality - Ge, Jun; Kang, Mincheol; Haile, Tegegne Tesfaye (International Journal of Asian Business and Information Management, 2021)
This study examines factors that influence users' continuance intention to use a mobile application. There exist few empirical researches focused solely on examining factors influencing users' continuance intention of using mobile applications. An empirical analysis is conducted with data collected from 431 smartphone users in China. Two application personality dimensions (i.e., enthusiasm and unpleasantness) and one user perception dimension (i.e., aesthetics) were found to have no significant impact on application continuance intention while genuineness and sophistication from application personality dimensions and ease of use and perceived control from user perception dimensions have a positive significant influence. This study provides an insight to application developers on how to improve the quality and usability of mobile applications and enhance continues use.
Keywords: Application personality; Application quality; Application usability; Continuance intention; Mobile application; User perception